Correlating Practicum Performance and Student Perceptions in Virtual Basic Physic III: A Mixed-Methods Study - Charlos Falentino; Anggara Duta Medika; Grecellia Mei Magdalena Dakhi; Alphero Tanlianto (Program Studi Pendidikan Fisika, 2025)
This study examines the perspectives and experiences of Physics education students regarding the virtual implementation of Basic Physics III practicum. Using a mixed method approach, data was collected from 30 students at Mulawarman University through purposive sampling. The analysis was conducted using Spearman's rho correlation test to measure the correlation of basic physics practicum grades I and II to III, Likert scale analysis to measure readiness and perspective, metaphor analysis and free response answers to analyze feelings and experiences.The results showed a moderate correlation between the final grades of Basic Physics practicum I and III, but there was no significant correlation between grades II and III. The Likert scale and metaphor analysis showed that students' experience was like a rollercoaster ride, where they felt happy when they understood but confused when they did not understand. This study also found that learning styles (auditory, visual, kinesthetic), did not have a significant influence on the final grade of Basic Physics III practicum. Thus, this study supports the need for improvement and provision of basic physics practicum III tools, to be able to maximize student understanding in learning.